2021
DOI: 10.1002/admi.202100903
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity Enhancement and Electronic Applications of 2D Ti3C2Tx MXene Materials

Abstract: Not applicable; b) Minimally intensive layer delamination; c) Vacuum assisted filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 188 publications
(228 reference statements)
0
9
0
Order By: Relevance
“…Owing to their high electrical conductivity derived from their 2D structures and elemental nature, MXenes have also gained considerable attention in the field of neural tissue engineering. 116 Nan et al developed Ti 3 C 2 T x MXene-coated electrospun PCL NGCs to enhance neurite regeneration and angiogenesis (Fig. 4F-L).…”
Section: Neuromuscular Tissue Engineering Using G Mxenes and Xenesmentioning
confidence: 99%
“…Owing to their high electrical conductivity derived from their 2D structures and elemental nature, MXenes have also gained considerable attention in the field of neural tissue engineering. 116 Nan et al developed Ti 3 C 2 T x MXene-coated electrospun PCL NGCs to enhance neurite regeneration and angiogenesis (Fig. 4F-L).…”
Section: Neuromuscular Tissue Engineering Using G Mxenes and Xenesmentioning
confidence: 99%
“…Mxene can also improve conductivity. The surface treatment, which removes -OH and -F termination groups, also produces Mxene with higher conductivity [18].…”
Section: Electric Conductormentioning
confidence: 99%
“…The surface defect engineering of MXenes exhibits a great effect on the electrical conductivity, electronic structure and redox ability. 167,168 For example, Gogotsi et al 169 reported that monolayer Ti 3 C 2 T x MXene akes with well-dened and clean edges and visually defect-free surfaces exhibited a eld-effect electron mobility of 2.6 AE 0.7 cm 2 V À1 s À1 and a low resistivity of 2.31 AE 0.57 mU m (4600 AE 1100 S cm À1 ). Chen et al 170 used acid molecular (hydrouoric acid) scissors to controllably tailor titanium atoms and obtain redox-active sites for pseudocapacitive reactions.…”
Section: Effect Of Atomic Defects On the Redox Ability Of Mxenesmentioning
confidence: 99%